Membangun Ekonomi Berkelanjutan: Kontribusi UMKM dalam Peningkatan Pendapatan Masyarakat - Fatimah Hafni Simanjuntak; Nadra Syahira Putri (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2025)
MSMEs play a vital role in national economic growth through job creation and poverty reduction. This literature study analyzes the contributions and challenges of MSMEs in the digital era. The results show that MSMEs make a significant contribution to GDP and community welfare, but face obstacles such as limited access to financing, low digital literacy, and technological and managerial limitations. Collaboration between the government, the private sector, and the community is needed to strengthen human resources, expand access to funding, and encourage the adoption of digital technology so that MSMEs can compete in the digital economy.